A Highly Sensitive Amperometric Immunosensor for Clenbuterol Detection in Livestock Urine. Issue 4 (21st August 2012) - Li, Shengxi; Zhang, Jiong; Deng, Wangping; Shen, Xizhong; Song, Shiping; Fan, Chunhai
Abstract We report a highly sensitive competitive‐type assay for multiplexing electrochemical detection of clenbuterol in pig urine using a 16‐sensor array. In this design, the clenbuterol was first conjugated with bovine serum albumin (BSA), and then the conjugates were immobilized on the electrode surface to compete with the free clenbuterol in the sample for specific antibody. Under the optimal conditions, the reproducibility of the clenbuterol electrochemical immunosensor was evaluated to be 3.4 % (coefficient of variation, CV) and the limit of detection was estimated to be 1.3 pg/mL. The very low detection limit was probably derived from the higher efficiency of the competitive immunoreaction caused by appropriate quantities of the clenbuterol immobilized on the 16‐sensor array and the suitable amount of anti‐clenbuterol antibody in the assay system.